Custom-Made Foot Orthoses Decrease Medial Foot Loading During Drop Jump in Individuals With Patellofemoral Pain. Issue 4 (July 2016) - Rathleff, Michael S.; Richter, Camilla; Brushøj, Christoffer; Bencke, Jesper; Bandholm, Thomas; Holmich, Per; Thorborg, Kristian
Abstract : Objective: To investigate the effect of foot orthoses on medial-to-lateral plantar forces during drop jump and single leg squat, and second, to explore the self-reported change in symptoms after 12 weeks of wearing the orthoses in individuals with patellofemoral pain (PFP). Design: Cohort study with 12 weeks of follow-up. Setting: Hospital setting. Participants: 23 adults with PFP. Interventions: Custom-made foot orthoses. Main Outcome Measures: Foot loading (plantar pressure) was collected from the most painful side during drop jump and single leg squat using pressure sensitive Pedar insoles. Primary outcome was the medial-to-lateral peak force under the forefoot during drop jump. The PFP syndrome severity score was used to measure self-reported improvement from baseline to follow-up. Results: Orthoses were associated with a significant 2.9%-point (95% confidence intervals: 0.7-5.1) reduction in peak medial-to-lateral force during drop jump. Individuals with a self-reported improvement after 12 weeks had a significant 4.2%-point larger reduction in medial-to-lateral foot loading during drop jump. Conclusions: This preliminary study showed that foot orthoses were associated with a decrease in medially directed foot loading among individuals with PFP. Individuals, who have an immediate decrease in the medial-to-lateral peak force after fitting the orthoses, were more likely to report improvements after 12 weeks of use.